Pengaruh Pembiayaan Akad Murabahah PNM MEKAR Syariah Terhadap Pertumbuhan Ekonomi Masyarakat Kelurahan Sampir Kecematan Taliwang - Buanita, Buanita; Agustina, Ahadiah; Hidayanti, Nur Fitri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
PNM was established as the government's struggle as a financial management body to promote, maintain and share small and medium enterprises (MSMEs). . The method of data collection is carried out by questionnaires, observations, interviews and documentation, as well as collecting data from numbers and interpreting them into tabulations. This study aims to determine the effect of financing the PNM MEKAAR syariah murabahah contract on the economic growth of the village community in Sampir Taliwang sub-district. The result of this study is that the effect of financing the PNM MEKAAR syariah murabahah contract on the economic growth of the Sampir village community with the help of capital affects the community who join a group and have managed their business well so that they can generate profits that can meet individual needs and family needs.